Evaluation of Boron Carbide powder stability under accelerated aging - Amruth Kaitheri; Johannes Ofstad; Elvia Anabela Chavez Panduro; Martin Oppegård; Sanosh Kunjalukkal Padmanabhan; Sudipto Pal; Antonio Alessandro Licciulli; Vidar Johannesen; Trygve Eidet; Kjell Wiik; Mari-Ann Einarsrud (Open Ceramics)
Boron carbide (B4C) is a hard and durable ceramic used in aerospace, nuclear reactors, ballistic protection, etc. The stability of B4C powders at ambient conditions has been investigated using accelerated ageing by heat treatment at 400 °C in controlled atmospheres. The degree of conversion of B4C increased in the following order: Argon (no reaction), humidified argon (∼4 %), synthetic air (∼13 %) and humidified synthetic air (∼19 %). In humidified atmosphere, the reaction product was boric acid due to cooling in the presence of humidity. The high conversion in humidified synthetic air suggests that humidity accelerates the oxidation, and a reaction mechanism is proposed to explain the enhanced rate of oxidation. It is anticipated that the observed oxidation reactions are not limited to 400 °C but will also occur at ambient temperatures. This agrees with observations of reduced quality of the B4C during storage in ambient atmosphere.